Hormonal assessment of participants in a long distance walk - Haroldo Silva de Souza; Thiago Veiga Jardim; Weimar Kunz Sebba Barroso; Priscila Valverde de Oliveira Vitorino; Ana Luiza Lima Souza; Paulo César Veiga Jardim (Diabetology & Metabolic Syndrome, 2019)
Abstract Background Exercise can disrupt homeostasis and trigger many adaptive responses in different hormonal axes. The study of hormonal interactions with physical activity is highly complex due to the number of variables, such as exercise duration, exercise intensity, individual level of training, circadian rhythm, nutritional status, and environmental conditions. Methods This study was performed to assess daily variations of thyroid hormones, cortisol, testosterone, insulin and glucose during moderate to high intensity aerobic physical activity for 5 consecutive days. Sample collection was performed at baseline in the morning and in the evening, immediately after finishing the activity, on the 4 initial days of the activity. Statistical analysis was performed using software STATA V14. Continuous variables are presented as means and standard deviations, while categorical variables are presented as absolute and percentage values. We used Shapiro–Wilk, Wilcoxon Sign, Mann–Whitney and Student’s T test, according the needs. Results The adrenocorticotropic axis showed an initial increase in the evening cortisol level compared to the baseline level in the morning (17.46 μg/dL and 15.97 μg/dL, respectively) and then exhibited a significant reduction between the 1st and 4th day of activity (17.46 μg/dL and 8.39 μg/dL, respectively; P = 0.001). The same pattern was observed for free thyroxine (T4) between the 1st and 4th day (1.31 and 1.14, respectively; P < 0.001). Conclusions Moderate to intense long duration physical activity resulted in little variation in the hormones assessed, with a trend toward reduced levels of cortisol and free T4. These findings highlight an adaptive hormonal mechanism in response to stress that is repeated daily, as shown by cortisol and thyroid function in our study.